Effects of the Full Coverage Policy of Essential Medicines on Inequality in Medication Adherence: A Longitudinal Study in Taizhou, China - Guo, Zhigang; Zheng, Liguang; Fu, Mengyuan; Li, Huangqianyu; Bai, Lin; Guan, Xiaodong; Shi, Luwen (Frontiers in Pharmacology, 2022)
The full coverage policy for essential medicines (FCPEMs) was proposed and implemented in Taizhou city of Zhejiang Province, China, to promote equal access and adherence to medicines. This study aimed to examine the effects of FCPEMs on the income-related inequality in medication adherence among local patients with hypertension or diabetes. We collected electronic health records of patients with hypertension or diabetes of three districts of Taizhou from 2011-2016. As the implementation schedule of the FCPEMs policy varied across districts, we applied a retrospective longitudinal study design and assigned records from one year before and three years following the implementation of FCPEMs as baseline and follow-up data. We thus generated a dataset with four-year longitudinal data. The concentration index (CI) and its decomposition method were employed to measure factors contributing to inequality in medication adherence and the role played by FCPEMs. The sample size rose from 264,836 at baseline to 315,677, 340,512 and 355,676 by each follow-up year, and the proportion of patients taking free medicines rose from 17.6% to 25.0% and 29.8% after FCPEMs implementation. The proportion of patients with high adherence increased from 39.9% at baseline to 51.6%, 57.2%, and 60.5% while CI decreased from 0.073 to -0.011, -0.029, -0.035. The contribution of FCPEMs ranked 2nd/13, 7th/13 and 2nd/13 after the implementation of FCPEMs. Changes in CI of medication adherence for every two years were -0.084, -0.018, -0.006, and the contribution of FCPEMs were -0.006, 0.006, 0.007, ranking the 2nd/13, 2nd/13 and 1st/13. Most changes in CI of medication adherence can be attributed to FCPEMs. The medication adherence of patients with hypertension or diabetes improved after the implementation FCPEMs in Taizhou, though inequality did not improve consistently. In general, FCPEMs could be a protective factor against the income-related inequalities in access and adherence to medicines. Future research is needed to investigate the change mechanism and the optimal design of similar interventions.